Native-speakerism in English teacher recruitment in Indonesian schools - Voorsmit, Stanley Chris; Sakhiyya, Zulfa (ELT Forum: Journal of English Language Teaching, 2025)
Despite growing recognition of the limitations of native-speakerism in English language education, Indonesian schools continue to grapple with it. This study investigates Indonesian schools’ perspectives on recruiting English teachers, specifically examining attitudes toward Native English-Speaking Teachers (NESTs) and Non-Native English-Speaking Teachers (NNESTs). Using a survey administered to 73 Indonesian school administrators, the research explored perceptions of teaching abilities, the capacity to address student learning difficulties, and departmental preferences regarding NESTs versus NNESTs. Respondents rated their agreement with Likert-scale statements concerning native and non-native speaker teaching abilities and recruitment preferences. The findings revealed that while NESTs were sometimes preferred, there was no consistent pattern of prioritizing them over qualified NNEST candidates, particularly within schools with an international curriculum. These findings contribute to ongoing discussions surrounding the phenomenon of native-speakerism within Indonesian English as a Foreign Language context. They highlight the complexities inherent in teacher recruitment practices and suggest that professional qualifications, rather than native-speaker status, should be the primary basis for teacher recruitment decisions, ultimately benefiting students through access to highly qualified educators regardless of their linguistic background.